Preparation of the anatase/TiO2(B) TiO2 by self-assembly process and the high photodegradable performance on RhB. Issue 11 (15th August 2016) - Zhang, Lixin; Zheng, Wenhui; Jiu, Hongfang; Zhu, Wenze; Qi, Guisheng
Abstract: The TiO2 samples, synthesized with different addition amount of titanium source, have been prepared by a bottom-up method employing inverse lamellar micelles as the template in a surfactant molecular self-assembly process. The products were characterized by X-ray diffraction (XRD), Raman, Field-emission scanning electron microscope (FESEM), Transmission scanning electron microscopy (TEM), X-ray photoelectron Spectroscopy (XPS), Nitrogen adsorption-desorption isotherms, Photoluminescence spectra (PL), UV–vis diffuse reflectance (DRS) and photodegradable tests. The results show that all samples are biphases TiO2 (anatase and TiO2 (B)). In addition, with the increment of titanium source, the microstructure of three samples have changed from small 3D aggregates to big 3D aggregates composed of 2D nanosheets, and the proportion of the anatase phase in three products and the specific surface area (BET) of the samples gradually increased, which not only can suppress the recombination of photogenerated electrons and holes, and can also enhance the photodegradable performance and the adsorption performance of three products on organic pollutants RhB. The 2.5-TiO2 Ss exhibited the best photodegradable performance among three samples. Meanwhile, the 2.5-TiO2 Ss also had a good cycle stability and low performance loss (8%).